Self-Directed Advising for Online Graduate Students - Kalpana Gupta (Adult Education Research Conference, 2018)
Self-directed advising provides advisees and advisors to take active roles in the advising process. During this roundtable session, the use of self-directed advising will be discussed to consider future implications.
Keywords: self-directed; advising; online education